Supervisory quality in Universiti Teknologi Mara: Supervisors' expectations towards quality supervision / Maryam Jameelah Hashim, Idris Osman and Joeaiza Juhari - Hashim, Maryam Jameelah; Osman, Idris; Juhari, Joeaiza (2012)
In alignment with the Malaysian government goals and mission of the Vice Chancellor of Universiti Teknologi MARA, Dato' Prof. Ir. Dr. Sahol Hamid Abu Bakar in upgrading UiTM to be one of the research universities in Malaysia, the university must meet a few criteria. One of it is producing a large quantity and quality of researcher including postgraduate students. In order to achieve this surmountable task, the university encouraged for more research from postgraduate students. However, some of these graduate students find difficulty in writing research paper due to less structure in research direction and in making arrangements with their supervisors. Therefore, this research aims are firstly to identify the relationship between supervisors' attitude with supervisory quality and second, to identify the relationship between supervisors' knowledge with supervisory quality. This study adopts quantitative research approach (both supervising lecturers and practical students) of Universiti Teknologi MARA Malaysia and the data were gathered through distributing questionnaires and personal interviews. Sample size will be 680 respondents selected randomly from a few campuses. Data collected will be analysed using the Regression Analysis Model in order to identify the relationship of supervisors' expectations towards supervisory quality. Supervisory quality performance was measured according to following aspects: Attitudes and Knowledge. The outcome shows the existance of significant relationship between attitude and knowledge with supervisory quality. It is hoped that once the supervisors have the information on the supervising process, they are in a better position to develop skills to teach the postgraduate students in writing a quality research which eventually will result in producing high profile human capital and at the same time achieving the RU status.